Anti-crack sand casting coating and preparation method thereof
Patent Information
- Application Number
- CN202611134042.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-07-29
AI Technical Summary
[0005]针对现有技术中铸造涂料在高温热冲击下易开裂、剥落的技术问题,本发明提供了一种抗裂纹砂型铸造涂料及其制备方法
本发明通过复合微球在中温段软化,吸收热应力并愈合微裂纹;载镁硅酸盐矿物复合纤维依托孔道结构对氧化镁实现限域负载,高温下多孔结构部分坍塌,缓释的纳米氧化镁与煅烧高岭土、硅溶胶反应形成微晶结构,平衡刚玉骨料高温体积膨胀;同时,载镁硅酸盐矿物复合纤维以矿物孔道限域为主、硅烷偶联剂表面改性为辅,减少游离镁释放,保障硅溶胶体系常温稳定性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of casting coating technology, specifically relating to a crack-resistant sand casting coating and its preparation method. Background Technology
[0002] Sand casting is a key forming process for manufacturing core components of high-end equipment in aerospace, automotive, and wind power industries. Casting coatings, as functional protective layers applied to the surface of sand molds, directly determine the surface quality, dimensional accuracy, and yield of the castings. In industrial production, these coatings are prone to cracking and peeling under the thermal shock of molten metal, prolonged heat treatment, and thermal cycling, leading to defects such as sand adhesion, sand inclusions, and porosity. This results in a scrap rate exceeding 40%, significantly increasing post-processing costs and even causing the direct scrapping of high-value castings. This has become a key technological bottleneck restricting the stable production of high-end castings.
[0003] Existing casting coatings are mostly formulated with high-refractory aggregates (such as zircon powder, brown corundum, and corundum powder) combined with inorganic binders (such as silica sol and water glass) and suspending agents (such as bentonite, attapulgite, and sepiolite). To improve the crack resistance of the coating, existing technologies mainly focus on introducing rigid ceramic phases, optimizing aggregate gradation, and adding nanomaterials to increase coating density. Chinese patent application CN104525851A discloses a high-temperature ceramicized erosion-resistant environmentally friendly casting coating, which uses zircon powder, corundum powder, and forsterite powder as refractory aggregates, silica sol as a binder, and directly adds components such as anhydrous magnesium chloride powder and magnesium oxide powder. The magnesium salts react with the aggregates within the casting temperature range, causing the coating to undergo a ceramicization transformation, thereby improving the high-temperature strength and erosion resistance of the coating. Chinese patent application CN114985674A discloses a magnesium-aluminum alloy casting coating and its preparation method. The coating's high-temperature stability is enhanced by using nano-zirconia powder, and yttrium oxide is introduced to refine the grains on the surface of the casting.
[0004] However, the existing technology still has the following problems: First, it lacks a stress buffering mechanism: when high-temperature molten metal comes into contact with the coating, the inorganic binder forms a rigid silicon-oxygen network at high temperatures, and the refractory aggregate undergoes lattice expansion when heated. The compressive stress generated by the aggregate expansion is violently coupled with the tensile stress generated by the sand mold constraint. Second, the problem of thermal expansion coefficient mismatch remains unresolved: there is a significant difference in thermal expansion between the refractory aggregate and the sand mold. During rapid heating, this difference will cause shear stress at the interface between the coating and the sand mold, exacerbating the tendency of the coating to crack. Third, the direct addition of alkaline active components such as magnesium oxide to the water-based silica sol system will cause magnesium ions to interact with the silanol groups on the surface of the silica sol particles, neutralizing the surface charge, compressing the double layer, and triggering the sol-gel transition. This will cause the coating to lose its fluidity, limiting the application of active magnesium sources in water-based casting coatings. Summary of the Invention
[0005] To address the technical problem of cracking and peeling of existing casting coatings under high-temperature thermal shock, this invention provides a crack-resistant sand casting coating and its preparation method.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: A crack-resistant sand casting coating comprises the following raw materials in parts by weight: 900-1100 parts brown corundum powder, 100-200 parts calcined kaolin, 430-530 parts silica sol, 80-100 parts magnesium silicate mineral composite fiber, 20-25 parts composite microspheres, 1-3 parts organic rheology modifier, 2-4 parts wetting agent, 1-3 parts defoamer, and 200-300 parts deionized water; The magnesium-loaded silicate mineral composite fiber is obtained by loading magnesium salt precursor into the pores of fibrous porous silicate mineral through a vacuum-pressure impregnation process, followed by drying and calcination, and then coating and modifying it with a silane coupling agent. The composite microspheres are obtained by mixing and melting zinc phosphate and boric acid, followed by liquid nitrogen rapid quenching and ball milling.
[0007] In this scheme, the pore structure of fibrous porous silicate minerals confines and loads magnesium oxide, which is then modified by a silane coupling agent to reduce the demulsification damage of free magnesium to the silica sol, thus maintaining excellent suspension stability of the coating at room temperature. When the coating is subjected to thermal shock, the composite microspheres soften first in the temperature range to form a glassy liquid film, absorbing thermal expansion stress and healing microcracks, preventing crack initiation. The magnesium-loaded silicate mineral composite fiber structure gradually collapses and releases magnesium oxide, which reacts with calcined kaolin and silica sol to form a microcrystalline structure, balancing the high-temperature volume expansion of corundum, thereby improving the coating's resistance to high-temperature thermal shock and preventing high-temperature cracking and peeling.
[0008] Preferably, the magnesium silicate mineral composite fiber is prepared by the following method: pretreated fibrous porous silicate minerals are mixed with a magnesium salt precursor solution, subjected to vacuum-pressure impregnation, dried, and calcined at 400-500℃ for 2-3 hours to obtain a solid product; the solid product is dispersed in an ethanol aqueous solution, the pH of the system is adjusted to 8-9, a silane coupling agent is added, the temperature is raised to 40-50℃ and stirred for 3-4 hours, filtered, and dried to obtain the magnesium silicate mineral composite fiber.
[0009] In this scheme, magnesium salt solution is forced into the depth of mineral channels through vacuum-pressure impregnation, and magnesium oxide is generated in situ in the silicate mineral channels through calcination. Then, a silane coupling agent is used to modify the surface of the magnesium silicate mineral composite fiber, which reduces the probability of direct contact between magnesium oxide and silica sol, and avoids silica sol demulsification and gelation, which would affect the room temperature stability of the coating.
[0010] Preferably, the pretreatment is an acidification pretreatment.
[0011] Preferably, the acidification pretreatment includes the following steps: adding fibrous porous silicate minerals to a hydrochloric acid solution, stirring for 0.5-1.5 hours, washing until neutral, and drying to obtain pretreated fibrous porous silicate minerals.
[0012] Preferably, the vacuum-pressure impregnation treatment includes the following steps: placing a pretreated fibrous porous silicate mineral and magnesium salt precursor solution in a reaction vessel, evacuating to an absolute pressure below 1000 Pa and maintaining it for 20-30 min, then introducing pressurized gas to a pressure of 0.2-0.4 MPa and maintaining the pressure for 30-40 min.
[0013] This technical solution achieves forced permeation of magnesium salt precursor solution through vacuum-pressurization cycle; during the vacuuming stage, gas in the pores is discharged to eliminate capillary resistance; during the pressurization stage, the solution is forced into the depth of the pores by pressure difference; the vacuum degree is below 1000Pa to ensure that gas in the pores is fully discharged, and the pressure of 0.2-0.4MPa provides sufficient driving force.
[0014] Preferably, the mass ratio of the pretreated fibrous porous silicate mineral to the magnesium salt precursor is 1:1-1.2.
[0015] Preferably, the magnesium salt precursor is one or more of magnesium nitrate or magnesium acetate.
[0016] Preferably, the fibrous porous silicate mineral is one or more of sepiolite and attapulgite.
[0017] In this scheme, both sepiolite and attapulgite have one-dimensional nanoporous structures and fibrous micromorphologies; their fibrous morphology can form a dense three-dimensional physical network in the coating, further improving suspension stability; and their nanopores provide an ideal confined space for magnesium salt precursors, ensuring that the active components remain nanoscale dispersed after calcination.
[0018] Preferably, the silane coupling agent is an aminosilane coupling agent.
[0019] Preferably, the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the amount of the silane coupling agent added is 8%-10% of the mass of the solid product.
[0020] Preferably, the composite microspheres are prepared by the following method: zinc phosphate and boric acid are mixed evenly and heated to 900-1000℃ and held at that temperature for 40-50 minutes to melt; the molten liquid is poured into liquid nitrogen for rapid quenching to obtain glassy fragments; and the composite microspheres are obtained by ball milling.
[0021] Preferably, the mass ratio of zinc phosphate to boric acid is 8-10:35.
[0022] Preferably, the ball milling is a wet ball milling process, the ball milling medium is anhydrous ethanol, the ball milling speed is 300-500 rpm, and the ball milling time is 4-6 h.
[0023] In this scheme, the optimization of the above parameters can obtain composite microspheres with uniform particle size and good dispersibility, which are convenient for uniform dispersion in coatings.
[0024] Preferably, the organic rheology modifier is sodium polyacrylate.
[0025] Preferably, the wetting agent is BYK-346 manufactured by BYK in Germany.
[0026] Preferably, the defoamer is BYK-024 manufactured by BYK in Germany.
[0027] This invention also provides a method for preparing a crack-resistant sand casting coating, comprising the following steps: S1: Construction of the basic liquid film system: Mix silica sol, deionized water, organic rheology modifier, wetting agent and defoamer evenly; S2: Cascaded high-shear composite mixture: Under stirring conditions, calcined kaolin, magnesium silicate mineral composite fiber, and composite microspheres are added sequentially to the basic liquid film system of step S1. After being mixed evenly, brown corundum powder is added and dispersed under high shear to obtain crack-resistant sand casting coating.
[0028] Preferably, in step S1, the stirring speed is 500-700 rpm.
[0029] Preferably, in step S2, the high-shear dispersion rotation speed is 800-1000 rpm and the dispersion time is 40-60 min.
[0030] In this scheme, high shear dispersion is the key step to ensure the uniform distribution of multiphase powder in the coating. The cascade feeding sequence (first adding calcined kaolin, magnesium-loaded mineral carrier, and composite microspheres, then adding brown fused alumina powder) avoids the interference of a large amount of added brown fused alumina powder on the dispersion of fine powder; ensuring that the components of the final coating are uniformly distributed, without macroscopic agglomeration, and have excellent workability.
[0031] This invention also provides an application of anti-crack sand casting coating in casting manufacturing.
[0032] The above-mentioned anti-crack sand casting coating is applied to the surface of the sand mold, and after drying, it is used to pour molten metal to obtain castings.
[0033] Compared with the prior art, the beneficial effects of the present invention are: This invention utilizes composite microspheres to soften in the mid-temperature range, absorbing thermal stress and healing microcracks. Magnesium-loaded silicate mineral composite fibers achieve confined loading of magnesium oxide through their porous structure. At high temperatures, the porous structure partially collapses, and the slowly released nano-magnesium oxide reacts with calcined kaolin and silica sol to form a microcrystalline structure, balancing the high-temperature volume expansion of corundum aggregate. Simultaneously, the magnesium-loaded silicate mineral composite fibers primarily confine the magnesium oxide within mineral pores, supplemented by surface modification with silane coupling agents, reducing the release of free magnesium and ensuring the room-temperature stability of the silica sol system.
[0034] The coating of this invention has excellent high-temperature crack resistance and suspension stability, and is suitable for sand casting process of high-end castings. Detailed Implementation
[0035] The technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0036] Unless otherwise specified, all raw materials used in the examples and comparative examples are commercially available.
[0037] Sepiolite: Natural sepiolite raw ore powder, sieved through 200 mesh; Attapulgite: sieved through 200 mesh; Brown corundum powder: Al2O3 content ≥95%, sieved through 300 mesh; Silica sol: solid content 30%; Calcined kaolin: sieved through 1250 mesh; Organic rheology modifier is sodium polyacrylate, with an average molecular weight of 3 million-5 million; Wetting agent is BYK-346 manufactured by BYK (Germany); Defoamer is BYK-024 manufactured by BYK (Germany).
[0038] Preparation Examples 1-4: Preparation of Magnesium Silicate Mineral Composite Fibers Preparation Example 1 (1) Add 1 kg of sepiolite raw ore powder to 5 L of 0.75 mol / L hydrochloric acid solution, turn on the stirrer, set the speed to 400 rpm, and stir at room temperature for 1 h; after the acid leaching is completed, filter through a sand core funnel and wash the filter cake with deionized water until the pH of the filtrate is neutral; place the filter cake in a forced-air drying oven to dry and obtain pretreated sepiolite powder; (2) Take 800g of pretreated sepiolite powder and mix it with 8.8kg of 10wt% magnesium nitrate solution and place it in a reaction vessel. Evacuate to an absolute pressure of 700Pa and maintain for 25min. Then, pressurize the gas to a pressure of 0.3MPa and maintain the pressure for 35min. After depressurization, take out the suspension, filter and dry it. Place the dried powder in a tube furnace and heat it to 450℃ at a heating rate of 5℃ / min in an air atmosphere. Calcinate at a constant temperature for 2.5h to obtain solid powder. (3) Take 800g of solid powder and disperse it in 8kg of 95vol% ethanol aqueous solution. Adjust the pH of the system to 8.5 with 28wt% ammonia water. Add 72g of γ-aminopropyltriethoxysilane, heat to 45℃ and stir for 3.5h. Filter and dry to obtain magnesium silicate mineral composite fiber.
[0039] Preparation Example 2 (1) Add 1 kg of sepiolite raw ore powder to 4 L of 0.5 mol / L hydrochloric acid solution, turn on the stirrer, set the speed to 300 rpm, and stir at room temperature for 1.5 h; after the acid leaching is completed, filter through a sand core funnel and wash the filter cake with deionized water until the pH of the filtrate is neutral; place the filter cake in a forced-air drying oven to dry and obtain pretreated sepiolite powder; (2) Take 800g of pretreated sepiolite powder and mix it with 8kg of 10wt% magnesium nitrate solution and place it in a reaction vessel. Evacuate the vessel to an absolute pressure of 600Pa and maintain it for 30min. Then, pressurize the vessel to a pressure of 0.2MPa and maintain the pressure for 40min. After depressurization, take out the suspension, filter and dry it. Place the dried powder in a tube furnace and heat it to 400℃ at a heating rate of 5℃ / min in an air atmosphere. Calcinate it at a constant temperature for 3h to obtain solid powder. (3) Take 800g of solid powder and disperse it in 8kg of 95vol% ethanol aqueous solution. Adjust the pH of the system to 8 with 28wt% ammonia water. Add 64g of γ-aminopropyltriethoxysilane, heat to 40℃ and stir for 4h. Filter and dry to obtain magnesium silicate mineral composite fiber.
[0040] Preparation Example 3 (1) Add 1 kg of sepiolite raw ore powder to 6 L of 1 mol / L hydrochloric acid solution, turn on the stirrer, set the speed to 500 rpm, and stir at room temperature for 0.5 h; after the acid leaching is completed, filter through a sand core funnel and wash the filter cake repeatedly with deionized water until the pH of the filtrate is neutral; place the filter cake in a forced-air drying oven to dry and obtain pretreated sepiolite powder; (2) Take 800g of pretreated sepiolite powder and mix it with 9.6kg of 10wt% magnesium nitrate solution and place it in a reaction vessel. Evacuate the vessel to an absolute pressure of 800Pa and maintain it for 20min. Then, pressurize the vessel to a pressure of 0.4MPa and maintain the pressure for 30min. After depressurization, take out the suspension, filter and dry it. Place the dried powder in a tube furnace and heat it to 500℃ at a heating rate of 5℃ / min in an air atmosphere. Calcinate it at a constant temperature for 2h to obtain solid powder. (3) Take 800g of solid powder and disperse it in 8kg of 95vol% ethanol aqueous solution. Adjust the pH of the system to 9 with 28wt% ammonia water. Add 80g of γ-aminopropyltriethoxysilane, heat to 50℃ and stir for 3h. Filter and dry to obtain magnesium silicate mineral composite fiber.
[0041] Preparation Example 4 Preparation Example 4 is basically the same as Preparation Example 1, except that sepiolite is replaced with an equal amount of attapulgite.
[0042] Preparation of composite microspheres in Examples 5-7 Preparation Example 5 Mix 9g of zinc phosphate powder and 35g of boric acid powder evenly, pour into an alumina crucible, place in a box-type resistance furnace, and heat to 950℃ at a rate of 10℃ / min under air atmosphere, holding at a constant temperature for 45min; until completely melted; quickly pour the molten high-temperature liquid mixture into a stainless steel container containing 1000mL of liquid nitrogen for rapid quenching; after the liquid nitrogen has completely evaporated, collect the glassy fragments at the bottom, place them in a planetary ball mill, add 500mL of anhydrous ethanol as the ball milling medium, and wet ball mill at 400rpm for 5h; after ball milling, remove the ethanol by rotary evaporation at 60℃ to obtain composite microspheres.
[0043] Preparation Example 6 Mix 8g of zinc phosphate powder and 35g of boric acid powder evenly, pour into an alumina crucible, place in a box-type resistance furnace, and heat to 900℃ at a rate of 10℃ / min under air atmosphere, holding at a constant temperature for 50min; until completely melted; quickly pour the molten high-temperature liquid mixture into a stainless steel container containing 1000mL of liquid nitrogen for rapid quenching; after the liquid nitrogen has completely evaporated, collect the glassy fragments at the bottom, place them in a planetary ball mill, add 500mL of anhydrous ethanol as the ball milling medium, and wet ball mill at 300rpm for 6h; after ball milling, remove the ethanol by rotary evaporation at 60℃ to obtain composite microspheres.
[0044] Preparation Example 7 Mix 10g of zinc phosphate powder and 35g of boric acid powder evenly, pour into an alumina crucible, place in a box-type resistance furnace, and heat to 1000℃ at a rate of 10℃ / min under air atmosphere, holding at a constant temperature for 40min; until completely melted; quickly pour the molten high-temperature liquid mixture into a stainless steel container containing 1000mL of liquid nitrogen for rapid quenching; after the liquid nitrogen has completely evaporated, collect the glassy fragments at the bottom, place them in a planetary ball mill, add 500mL of anhydrous ethanol as the ball milling medium, and wet ball mill at 500rpm for 4h; after ball milling, remove the ethanol by rotary evaporation at 60℃ to obtain composite microspheres.
[0045] Example 1 The preparation method of the anti-crack sand casting coating in this embodiment includes the following steps: S1. Construction of the basic liquid film system: Add 480g of silica sol (solid content of 30%), 250g of deionized water, 2g of organic rheology modifier, 3g of wetting agent and 2g of defoamer to the cylinder of a high-speed disperser in sequence; turn on the mechanical stirrer, set the speed to 600rpm, and stir continuously for 20min to obtain a uniform and slightly viscous colloidal basic liquid. S2. Cascaded high-shear composite mixing: While maintaining the disperser speed at 600 rpm, slowly and evenly add 150 g of calcined kaolin, 90 g of magnesium silicate mineral composite fiber (from preparation example 1), and 23 g of composite microspheres (from preparation example 5) in sequence. After the addition is complete, increase the speed to 900 rpm; then pour in 1 kg of brown corundum powder at a uniform speed, and continue to disperse at 900 rpm for 50 min to obtain a grayish-white casting coating.
[0046] Example 2 The preparation method of the anti-crack sand casting coating in this embodiment includes the following steps: S1. Construction of the basic liquid film system: Add 430g of silica sol (solid content of 30%), 200g of deionized water, 1g of organic rheology modifier, 2g of wetting agent and 1g of defoamer to the cylinder of a high-speed disperser in sequence; turn on the mechanical stirrer and set the speed to 500rpm and stir continuously for 25min to obtain a uniform and slightly viscous colloidal basic liquid. S2, Cascaded high-shear composite mixing: While maintaining the disperser speed at 500 rpm, slowly and evenly add 100 g of calcined kaolin, 80 g of magnesium silicate mineral composite fiber (from preparation example 2), and 20 g of composite microspheres (from preparation example 6) in sequence; after the addition is complete, increase the speed to 800 rpm and perform high-shear dispersion for 35 min; then uniformly pour in 900 g of brown corundum powder and continue to disperse at 800 rpm for 60 min to obtain a grayish-white casting coating.
[0047] Example 3 The preparation method of the anti-crack sand casting coating in this embodiment includes the following steps: S1. Construction of the basic liquid film system: Add 530g of silica sol (solid content of 30%), 300g of deionized water, 3g of organic rheology modifier, 3g of wetting agent and 3g of defoamer to the cylinder of a high-speed disperser in sequence; turn on the mechanical stirrer and set the speed to 700rpm and stir continuously for 15min to obtain a uniform and slightly viscous colloidal basic liquid. S2, Cascaded high-shear composite mixing: While maintaining the disperser speed at 700 rpm, slowly and evenly add 200 g of calcined kaolin, 100 g of magnesium silicate mineral composite fiber (from preparation example 3) and 25 g of composite microspheres (from preparation example 7) in sequence; after the addition is complete, increase the speed to 1000 rpm and perform high-shear dispersion for 25 min; then uniformly pour in 1100 g of brown corundum powder and continue to disperse at 1000 rpm for 40 min to obtain a grayish-white casting coating.
[0048] Example 4 Example 4 is basically the same as Example 1, except that the magnesium silicate mineral composite fiber is from Preparation Example 4.
[0049] Example 5 Example 5 is basically the same as Example 1, except that the composite microspheres are derived from Preparation Example 6.
[0050] Example 6 Example 6 is basically the same as Example 1, except that the composite microspheres are derived from Preparation Example 7.
[0051] Comparative Example 1 Comparative Example 1 is basically the same as Example 1, except that the amount of magnesium silicate mineral composite fiber added is 50g.
[0052] Comparative Example 2 Comparative Example 2 is basically the same as Example 1, except that the magnesium silicate mineral composite fiber is replaced by an equal amount of the solid powder prepared in step (2) of Preparation Example 1.
[0053] Comparative Example 3 Comparative Example 3 is basically the same as Example 1, except that the magnesium silicate mineral composite fiber is replaced with an equal amount of pretreated sepiolite powder prepared in step (1) of Preparation Example 1.
[0054] Comparative Example 4 Comparative Example 4 is basically the same as Example 1, except that the addition of composite microspheres was omitted.
[0055] Performance testing The performance of the casting coatings prepared in Examples 1-6 and Comparative Examples 1-4 was tested. The viscosity was tested according to the standard GB / T1723-1993 "Determination of Viscosity of Coatings", and the flow time of the coating at 25°C was determined by the Forte-4 cup method. The 24-hour sedimentation rate was tested according to the standard JB / T9226-2008 "Coatings for Sand Casting", and the sedimentation rate of the coating was tested by the graduated cylinder method after standing for 24 hours.
[0056] The thermal shock resistance test was conducted as follows: the coating was uniformly applied to the surface of a 50mm×50mm×10mm silica sand test block with a coating thickness of 1.0mm, and dried in a 200℃ oven for 1 hour. Subsequently, the test block was quickly pushed into a high-temperature box furnace that had been heated to 1000℃, 1300℃, and 1500℃ respectively and kept at that temperature for 20 minutes. After that, it was immediately removed and forced to cool in room temperature air. The surface morphology of the coating was then observed. The test results are shown in Table 1.
[0057] Table 1 Performance test results of coatings
[0058] Room temperature process performance analysis: As shown in Table 1, the viscosity values of the casting coatings prepared in Examples 1-6 at the Forte 4 cup ranged from 20.8 to 22.8 s, which is within the recommended application viscosity range for coatings used in sand casting, demonstrating good rheological properties and coating adaptability. Meanwhile, their 24-hour settling rate was only 2.5%-3.5%, indicating that the coatings have excellent suspension stability and can meet the uniformity requirements for long-term storage and on-site use.
[0059] Compared to Example 1, Comparative Example 1 showed a weaker physical network structure and increased sedimentation rate due to insufficient addition of magnesium-loaded silicate mineral composite fibers. The viscosity and sedimentation rate of Comparative Example 2 were significantly higher than those of Example 1. The reason for this is that the surface of the unmodified magnesium-loaded silicate mineral fibers contained exposed nano-magnesium oxide, which reacted locally with silica sol particles to form a microgel structure, leading to decreased system fluidity and deteriorated suspension. This demonstrates that in the magnesium-loaded silicate mineral composite fibers of this invention, the one-dimensional nanoporous structure of the fibrous silicate minerals provides a confined space for the magnesium source, and the silane coupling agent modification effectively prevents direct contact between nano-magnesium oxide and silica sol, avoiding gelation reactions.
[0060] High-temperature thermal shock resistance analysis: As shown in Table 1, the casting coatings prepared in Examples 1-6 all remained intact and crack-free after thermal shock at 1000℃, 1300℃, and 1500℃, demonstrating excellent high-temperature crack resistance. This is attributed to the three-level synergistic mechanism of "confined load-intermediate temperature buffer-high temperature anchoring" constructed in this invention: the composite microspheres soften in the intermediate temperature range to form a glassy liquid film, absorbing thermal expansion stress and healing microcracks, thus endowing the coating with "high-temperature plasticity"; as the temperature rises, the magnesium silicate mineral composite fiber structure gradually collapses, slowly releasing nano-magnesium oxide, which reacts with calcined kaolin and silica sol to form a microcrystalline structure, balancing the high-temperature volume expansion of corundum aggregate and eliminating the stress caused by thermal expansion mismatch from the root.
[0061] Compared to Example 1, the amount of magnesium silicate mineral composite fiber added in Comparative Example 1 was insufficient, resulting in network cracks in the coating at 1300℃. This indicates that the release of nano-magnesium oxide at high temperatures was insufficient to balance the thermal expansion differences of the corundum aggregate. In Comparative Example 2, the magnesium silicate mineral fiber was not modified by silane coupling agent coating, and microcracks appeared at 1300℃. This was because the exposed nano-magnesium oxide partially disrupted the stability of the silica sol system at room temperature, thereby damaging the coating uniformity and resulting in poor high-temperature thermal shock resistance. In Comparative Example 3, sepiolite was pretreated with acid but not loaded with a magnesium source, lacking high-temperature reactivity and unable to achieve structural anchoring, resulting in network cracks at 1300℃. In Comparative Example 4, no composite microspheres were added, and the lack of a mid-temperature buffering mechanism prevented the coating from effectively absorbing initial thermal stress, causing network cracks to appear at 1000℃.
[0062] In summary, this invention achieves a balance between high stability of the coating at room temperature and dynamic adaptive crack resistance at high temperature through a three-level synergistic mechanism of "limited load - medium-temperature buffer - high-temperature anchoring". The magnesium silicate mineral composite fiber ensures excellent suspension stability and application performance of the coating; the synergistic effect of the composite microspheres and the magnesium silicate mineral composite fiber at both medium and high temperatures allows the coating to remain intact and crack-free across a wide temperature range of 1000-1500℃.
[0063] The above are preferred embodiments of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A crack-resistant sand casting coating, characterized in that, The raw materials include the following parts by weight: 900-1100 parts brown fused alumina powder, 100-200 parts calcined kaolin, 430-530 parts silica sol, 80-100 parts magnesium silicate mineral composite fiber, 20-25 parts composite microspheres, 1-3 parts organic rheology modifier, 2-4 parts wetting agent, 1-3 parts defoamer, and 200-300 parts deionized water; The magnesium-loaded silicate mineral composite fiber is obtained by loading magnesium salt precursor into the pores of fibrous porous silicate mineral through a vacuum-pressure impregnation process, followed by drying and calcination, and then coating and modifying it with a silane coupling agent. The composite microspheres are obtained by mixing and melting zinc phosphate and boric acid, followed by liquid nitrogen rapid quenching and ball milling.
2. The anti-crack sand casting coating according to claim 1, characterized in that, The magnesium silicate mineral composite fiber is prepared by the following method: pretreated fibrous porous silicate mineral is mixed with magnesium salt precursor solution, subjected to vacuum-pressure impregnation treatment, dried, and then calcined at 400-500℃ for 2-3 hours to obtain solid product. The solid product was dispersed in an aqueous ethanol solution, the pH of the system was adjusted to 8-9, a silane coupling agent was added, the temperature was raised to 40-50℃ and the mixture was stirred for 3-4 hours, filtered and dried to obtain magnesium silicate mineral composite fibers.
3. The anti-crack sand casting coating according to claim 2, characterized in that, The mass ratio of the pretreated fibrous porous silicate mineral to the magnesium salt precursor is 1:1-1.
2.
4. The anti-crack sand casting coating according to claim 2, characterized in that, The magnesium salt precursor is one or more of magnesium nitrate or magnesium acetate.
5. The anti-crack sand casting coating according to claim 2, characterized in that, The fibrous porous silicate mineral is one or more of sepiolite and attapulgite.
6. The anti-crack sand casting coating according to claim 2, characterized in that, The silane coupling agent is an aminosilane coupling agent.
7. The anti-crack sand casting coating according to claim 6, characterized in that, The aminosilane coupling agent is γ-aminopropyltriethoxysilane; the amount of the silane coupling agent added is 8%-10% of the mass of the solid product.
8. The anti-crack sand casting coating according to claim 1, characterized in that, The composite microspheres were prepared by the following method: zinc phosphate and boric acid were mixed evenly and heated to 900-1000℃ and held for 40-50 minutes to melt; the molten liquid was poured into liquid nitrogen for rapid quenching to obtain glassy fragments; and the composite microspheres were obtained by ball milling.
9. The anti-crack sand casting coating according to claim 8, characterized in that, The mass ratio of zinc phosphate to boric acid is 8-10:
35.
10. The method for preparing the anti-crack sand casting coating according to any one of claims 1-9, characterized in that, Includes the following steps: S1. Construction of the basic liquid film system: Mix silica sol, deionized water, organic rheology modifier, wetting agent and defoamer evenly; S2, Cascaded High-Shear Composite Mixture: Under stirring conditions, calcined kaolin, magnesium silicate mineral composite fiber, and composite microspheres are added sequentially to the basic liquid film system of step S1. After being mixed evenly, brown corundum powder is added and dispersed under high shear to obtain crack-resistant sand casting coating.
Citation Information
Patent Citations
High-temperature, ceramic, erosion-resistant, dust-pollution-free and environment-friendly casting coating
CN104525851A
Magnesium-aluminum alloy casting coating, preparation method and equipment thereof and readable storage medium
CN114985674A
Anti-cracking casting coating based on attapulgite
CN108543909A
Sand casting water-based paint and preparation method thereof
CN120325889A
